The Practicality of Model Introduction, Connection, Application, Reflection, and Extension-Paradigm of Reflective Pedagogy with BioPhy Magazine for Optimizing Learning - Ita Ita*; Lutfiyanti Fitriah (Jurnal Pendidikan Sains Indonesia, 2022)
Learning outcomes in basic physics courses still show a low average score for students. This shows that the learning process has not achieved the expected target. It was necessary to innovate to overcome these problems by developing models and teaching materials. The purpose of this study was to describe the practicality of the introduction, connection, application, reflection, and extension-paradigm of reflective pedagogy learning model and the practicality of using biophy magazine teaching materials. This research is part of educational design research to the stage of formative evaluation test on a one-to-one, small group and field test. Data on the practicality of the learning model were obtained through observations of the implementation of learning carried out by two observers. Data on the practicality of teaching materials were obtained from questionnaires given to students. Based on these results, practicality of models and teaching materials were then categorized into five categories, very practical, practical, quite practical, less practical, and very less practical. The results showed that the lecturers had carried out each stage very well so that the results of the observer's assessment showed a very practical category in individual, small group and field tests. Student activities were classified as very practical in individual tests and field tests, while in small group trials, they were quite practical. Therefore, ICARE-PPR learning was classified as very practical. Biophy Magazine's teaching materials based on the floating market as a result of development are also classified as very practical with easy, efficient, useful and attractive for students